Literature Review: Efek Pemberian Kinesio Taping terhadap Nyeri pada Pasien Osteoartrithis Lutut - Muhammad Daris Izdihar Putera Negara; Muhammad Siddik; Didik Dwi Sanyoto (Homeostasis, 2021)
Abstract: Kinesio Taping is emerging as an interesting method that can be applied to any condition of musculoskeletal injury. Likewise with osteoarthritis. This literature review was conducted with the aim of providing an overview of the effects of kinesio taping on pain in patients with knee osteoarthritis. The search was carried out on English-language articles published between 2010-2020. The articles used in this literature review are eight articles. The results of the literature review show that there is a positive effect of kinesio taping on pain in patients with knee osteoarthritis. This is evidenced by the reduction in pain measurement scores in almost all studies. There are several variations of KT fitting for knee OA, however, the Space correction technique is believed to be the fastest technique in reducing or eliminating pain in knee OA. Keywords: knee osteoarthritis kinesiotaping pain, kinesio taping, kneeosteoarthritis. Abstrak: Kinesio Taping muncul sebagai metode menarik yang dapat diterapkan pada berbagai kondisi cidera muskuloskeletal apa pun. Begitu juga dengan Osteoarthritis. Tinjauan literatur ini dilakukan dengan tujuan untuk memberikan gambaran umum terkait efek pemberian kinesio taping terhadap nyeri pada pasien Osteoarthritis lutut. Penelusuran dilakukan pada artikel berbahasa Inggris yang diterbitkan antara tahun 2010-2020. Artikel yang digunakan dalam tinjauan literatur ini sebanyak delapan artikel. Hasil tinjauan literatur menunjukkan bahwa terdapat efek positif pemberian kinesio taping terhadap nyeri pada pasien Osteoarthritis lutut. Hal ini dibuktkan dengan penurunan skor pengukuran nyeri di hampir semua penelitian. Terdapat beberapa variasi pemasangan KT untuk OA lutut, namun teknik Space correction dipercaya sebagai teknik tercepat dalam mengurangi atau menghilangkan nyeri pada OA lutut. Kata-kata kunci: knee osteoarthritis kinesiotaping pain, kinesio taping, kneeosteoarthritis